Fostering Caring Attributes to Improve Patient Care in Nursing Through Small-Group Work: Perspectives of Students and Educators - Florence Mei Fung Wong (Nursing Reports)
Background: Nursing relies on the development of caring attributes to uphold exceptional standards of care. While small-group work is a common practice in nursing education, its pivotal role in nurturing these attributes often remains underexplored. Aim: This study explored how caring attributes emerge in small-group settings from the perspectives of nursing students and educators. Methods: This qualitative study conducted semi-structured group interviews separately for students and educators. Thirteen nursing students and ten educators at a professional educational institution were interviewed. Results: Through the interviews, four key sets of caring attributes nurtured through small-group work were identified: interpersonal communication with respect; compassion and empathy; competence and confidence; and accountability to commitment. These findings, based on the perspectives of students and educators, underscore the essential role of caring in nursing. They emphasize how collaborative group work can serve as a catalyst for the development of these vital attributes through meaningful interpersonal interactions. Notably, the cultivation of respectful communication skills among students emerged as pivotal for enriching interactions with healthcare professionals, patients, and families, ultimately enhancing the quality of care provided. By providing a platform for interactive learning and continual practice, small-group work facilitates the internalization of these caring attributes, nurturing nursing professionalism over the course of students’ careers. Conclusions: This study offers invaluable insights into the profound impact of small-group work in fostering caring attributes and propelling advancements in nursing education and practice. By enhancing the development of these attributes, small-group work contributes to the delivery of compassionate and high-quality patient care.